Screening of Urological Anomalies Associated with Anorectal Malformations in Children: Single-Center Experience in Two Years - oshiba, ahmed; megeleka paul , Marco; khairi gabr , Ahmed; abdelazim abouheba, Mohamed (Iranian Journal of Pediatric Surgery, 2025)
Abstract Introduction: Urological anomalies are the most common associated anomalies in patients with anorectal malformations (ARM). Most publications state an incidence between 30% and 50%, with the frequency of the coincidence increasing proportionally with the complexity of anorectal malformations. Therefore, in order to enable early diagnosis and management of these abnormalities, a high index of suspicion is needed. In addition, long-term follow-up of patients with anorectal malformations and surveillance of their kidney function and urinary tract anatomy is of great importance to prevent damage to the urinary system. To identify and classify the urological anomalies associated with anorectal malformation patients admitted to Pediatric Surgery department in Alexandria University Children’s Hospital from June 2021 to June 2023 and to correlate urological anomalies with the level of anorectal malformation. Material and Methods: This study involved collection of data of all patients diagnosed with anorectal malformations between June 2021 and June 2023 who attended at Alexandria Pediatric Surgery Department of Alexandria University Children’s Hospital. Including: patients who were diagnosed with anorectal malformations and underwent urological screening. The following data were extracted from the patient’s files who met the inclusion criteria: neonatal presentation, age at presentation, weight, sex and findings of genital examination. Results: In 66 patients with ARM, 19(28.7%) patients had low anorectal anomaly (LARA) and high rectal anomaly (HARA) were found in 47(71.2%) patients. The incidence of ARM was higher in male patients than in female patients regardless the level of ARM. The most common genital anomaly among male patients was bifid scrotum, which was found in 3 out of 15 with genital anomaly, followed by hypospadias. In female patients, isolated cloaca anomaly was the most frequent genital anomaly. Conclusion: screening of associated urological anomalies is vital to prevent renal damage and reduce morbidity and mortality in patients with anorectal malformations.